Lexical categorization of rape and lewd in Malay tabloid / Ain Nadhirah Mohd Shah - Mohd Shah, Ain Nadhirah (2021)
The categorization of meaning is an issue that is seen as very important. This is because a word is not only limited to one meaning but it can also lead to a variety of different meanings such as words that are polysemous. A word needs to be understood in its lexical meaning because it can give a certain effect to the context and phrase. Dedi Sutedi (2016), states that when a person receives information, it will be processed and go through several stages that eventually become knowledge and stored in one's mind. The process of storing this information occurs through several stages and one of them is the categorization process. This categorization process is used to categorize the core meaning and the fringe meaning of a word, especially words that have many meanings or that have a circle of meaning. The meaning of a word can be known by taking into account several factors such as experience, culture, context, emotions, and so on. Therefore, the choice of words when debating an issue is an aspect that needs to be emphasized in addition to being accurate and appropriate to the context so that the meaning to be conveyed is clear and does not cause misunderstanding. When debating about word choice and clear and effective presentation of information, it is so synonymous with the role of the media. This is because the media plays a role as a mediator in conveying information to the public. Furthermore, society today is seen to be easily influenced by what it reads, sees, and hears. Therefore, it is not an exaggeration to say that the media has an important role in conveying information to the public. Therefore, this study aims to identify and analyze the categorization of meaning and lexical selection to describe the crime of rape and obscenity in newspapers using Prototype Theory as well as produce Lexical Mapping Model of Rape and Obscenity using Lexical Mapping Model by Heider (1991). The study also proves that the Lexical Mapping Model can be utilized to help the process of understanding to agree with and help the reader resolve the ambiguity of meaning so that the true meaning of the language can be obtained.